Immune checkpoint inhibitors and Chimeric Antigen Receptor (CAR)-T cell therapy: Potential treatment options against Testicular Germ Cell Tumors - Schepisi, Giuseppe; Gianni, Caterina; Cursano, Maria Concetta; Gallà, Valentina; Menna, Cecilia; Casadei, Chiara; Bleve, Sara; Lolli, Cristian; Martinelli, Giovanni; Rosti, Giovanni; De Giorgi, Ugo (Frontiers in Immunology, 2023)
Germ cell tumors (GCTs) represent a heterogeneous neoplasm family affecting gonads and rarely occurring in extragonadal areas. Most of patients have a good prognosis, often even in the presence of metastatic disease; however, in almost 15% of cases, tumor relapse and platinum resistance are the main challenges. Thus, novel treatment strategies with both improved antineoplastic activity and minor treatment-related adverse events compared with platinum are really expected. In this context, the development and the high activity demonstrated by immune checkpoint inhibitors in solid tumors and, subsequently, the interesting results obtained from the use of chimeric antigen receptor (CAR-) T cell therapy in hematological tumors, have stimulated research in this direction also in GCTs. In this article we will analyze the molecular mechanisms underlying the immune action in the development of GCTs, and we will report the data from the studies that tested the new immunotherapeutic approaches in these neoplasms.